2013
DOI: 10.1021/jo400702z
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-Catalyzed Hydroxylation of Aryl Halides Using Glycolic acid as a Ligand

Abstract: Copper(II)-catalyzed hydroxylation of aryl halides has been developed to afford functionalized phenols. The protocol utilizes the reagent combination of Cu(OH)2, glycolic acid, and NaOH in aqueous DMSO, all of which are cheap, readily available, and easily removable after the reaction. A broad range of aryl iodides and activated aryl bromides were transformed into the corresponding phenols in excellent yields. Moreover, it has been shown that C-O(alkyl)-coupled product, instead of phenol, can be predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 37 publications
(81 reference statements)
2
29
0
Order By: Relevance
“…To the best of our knowledge,o nly Xiao et al [26] has reported av alid procedure for performing aC u/Pd-catalysed cross-coupling between an aryl bromide/iodide and an alpha-hydroxy acid. To the best of our knowledge,o nly Xiao et al [26] has reported av alid procedure for performing aC u/Pd-catalysed cross-coupling between an aryl bromide/iodide and an alpha-hydroxy acid.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge,o nly Xiao et al [26] has reported av alid procedure for performing aC u/Pd-catalysed cross-coupling between an aryl bromide/iodide and an alpha-hydroxy acid. To the best of our knowledge,o nly Xiao et al [26] has reported av alid procedure for performing aC u/Pd-catalysed cross-coupling between an aryl bromide/iodide and an alpha-hydroxy acid.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the scope of the title reaction, we investigated the reactions using bromobenzene, chlorobenzene and 2-iodine thiophene as the substrates under the optimized reaction conditions. The results are listed in Table 2 (entries [16][17][18][19]. As shown in Table 2, in our catalytic system, aryl bromides and chlorides were inert under the experimental conditions giving no cross-coupling products ( Table 2, entries 16 and 17).…”
mentioning
confidence: 85%
“…Encouraged by these good results, the effects of concentrations of bases, reaction temperature and reaction solvents on the phenol synthesis were further investigated. It is worth noting that at lower concentrations of the bases or when the temperature was below 120 1C, the yield of phenol was low ( 18). To further optimize the reaction conditions, the effect of the amount of Cu-g-C 3 N 4 catalyst on the reaction was studied.…”
mentioning
confidence: 99%
“…In 2013, the Chae group reported that a simple ligand, glycolic acid, could promote the conversion of aryl halides to phenols in the presence of Cu(OH) 2 and NaOH in the solvent of DMSO/H 2 O (1:1) (Scheme 15) [37]. Aryl iodides can give the corresponding phenols in excellent yields.…”
Section: Reviewmentioning
confidence: 99%